Pengaruh Peran Internal Audit terhadap Kualitas Laporan Keuangan Inspektorat Kota Ambon dan Provinsi Maluku - Tomasoa, Theodora Florence; Manuhuttu, Silvia (Universitas Pattimura, 2022)
The quality of local government financial reports is often suboptimal due to weak internal oversight by inspectorates. This study aims to analyze the effect of the internal audit function on the quality of financial reports at the Inspectorate of Ambon City and Maluku Province. The research employed a quantitative approach using questionnaires and simple linear regression analysis. The population consisted of 60 internal auditors, who also served as the sample through the census method. The results revealed that internal audit roles have a positive and significant effect on financial reporting quality, as evidenced by the t-value exceeding the critical threshold. These findings suggest that strengthening the internal audit function enhances the reliability, relevance, and comparability of financial reports. There is a need to build professional auditor capacity and enforce oversight standards based on regulations. It is recommended that local governments reassess internal audit strategies and provide competency-based technical training for supervisory personnel